New insights into muscle activity associated with phantom hand movements in transhumeral amputees - Chateaux, Manon; Rossel, Olivier; Vérité, Fabien; Nicol, Caroline; Touillet, Amélie; Paysant, Jean; Jarrassé, Nathanaël; De Graaf, Jozina B. (Frontiers in Human Neuroscience, 2024)
Muscle activity patterns in the residual arm are systematically present during phantom hand movements (PHM) in transhumeral amputees (Raffin et al., 2012). However, their characteristics have not been directly investigated yet, leaving their neurophysiological origin poorly understood. This study pioneers a neurophysiological perspective in examining PHM-related muscle activity patterns by characterizing and comparing them with those in the arm, forearm, and hand muscles of control participants executing intact hand movements (IHM) of similar types. To enable rigorous comparison, we developed meta-variables independent of electrode placement, quantifying the phasic profile of recorded surface EMG signals and the specificity of their patterns across electrode sites and movement types. Similar to the forearm and hand muscles during IHM, each signal recorded from the residual upper arm during PHM displays a phasic profile, synchronized with the onset and offset of each movement repetition. Furthermore, the PHM-related patterns of phasic muscle activity are specific not only to the type of movement but also to the electrode site, even within the same upper arm muscle, while these muscles exhibit homogeneous activities in intact arms. Our results suggest the existence of peripheral reorganization, eventually leading to the emergence of independently controlled muscular sub-volumes. This reorganization potentially occurs through the sprouting of severed axons and the recapture of muscle fibres in the residual limb (Woo et al., 2016). Further research is imperative to comprehend this mechanism and its relationship with PHM, holding significant implications for the rehabilitation process and myoelectric prosthesis control.